PENANAMAN NILAI-NILAI MODERASI BERAGAMA PESERTA DIDIK PADA KEGIATAN KEROHANIAN ISLAM (ROHIS) DI MADRASAH ALIYAH NEGERI 1 KOLAKA - Sartika; Nurhayati; Ade Saputra (Jurnal Teknologi Pendidikan Madrasah, 2023)
Religious moderation is seen and religious attitudes and practices that reflect the true meaning of religious teachings from well-known communities and spread benefits are called madrasah are the first place to make changes, in order to shape the morals and morals of students through Islamic spiritual activities (Rohis). The iam of this research is 1) To find out the implementation of religious moderation values in the participant of Madrasah Aliyah Negeri 1 Kolaka, 2) To find out the implementation of activities Islamic spirituality (Rohis) at Madrasah Aliyah Negeri 1 Kolaka, 3) To find out what the supporting and inhibiting factors are instilling religious moderation values in islamic spiritual activities (Rohis) at Madrasah Aliyah Negeri 1 Kolaka. The research method used includes a qualitative approach to phenomenological research. The research subjects were resident of Madrasah Aliyah Negeri 1 Kolaka consisting of the Madrasah Head, teachers and students. Data collection methods used included observation, interviews, documentation. The results of this research show that 1) there is an instillation of moderation religious values in students through Islamic spiritual activities (Rohis) at Madrasah Aliyah Negeri 1 Kolaka. Moderation values are instilled in accordance with the focus of study in the from of tawassuth, tasamuh or tolerance (infaq). Friday which is held every Friday and ramadan safari which is held once a year in the holy month of ramadan) I’tidal. Qudwah (carrying out dhuha prayers, zikir, zuhur prayers, tadarrus, kultum every day, and commemorating major Islamic holidays once a year) 2) Islamic spiritual activities (Rohis) have been carried out well with several activities, namely a) Dhuha and zikir prayers together, b) zuhur prayers in congregation ah tadarrus and kultum, c) celebration of the great Islamic holiday, d) safari ramadan. e) infaq furn at through this activity, students are taught the values of religious moderation and directly put into practice using the discussion method and the practical method of activities, which are coached directly by the supervisor teacher. This activity is an activity carried out outside of class with the iam of increasing and broadening knowledge. Students in the lessons learned 3) supporting factors, namely the quality of professional teachers, a religious culture and adequate facilities. While the inhibitors are the influence of social media, an environment that is not conducive.